2013
DOI: 10.1016/j.jcrs.2012.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Topography-guided transepithelial photorefractive keratectomy for irregular astigmatism using a 213 nm solid-state laser

Abstract: 213 nm topography-guided transepithelial PRK was easy to perform and well tolerated by patients with irregular astigmatism. Most patients gained CDVA; however, increased haze responses were observed in post-keratoplasty cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Undercorrection is generally recommended for TG-PRK, as significant irregular astigmatism can preclude an appropriate evaluation of manifest refraction, and differential ablation rates may contribute to additional uncertainty. 8,10 Altogether, our results and the remaining available small series suggest that TG-PRK offers a valuable option for irregular astigmatism in eyes post-CT. Ablating only the localized defects removes less tissue than correcting a similar amount of regular astigmatism. This sparing of corneal tissue allows treatment of high levels of irregular astigmatism, simultaneously achieving a regular smooth surface.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Undercorrection is generally recommended for TG-PRK, as significant irregular astigmatism can preclude an appropriate evaluation of manifest refraction, and differential ablation rates may contribute to additional uncertainty. 8,10 Altogether, our results and the remaining available small series suggest that TG-PRK offers a valuable option for irregular astigmatism in eyes post-CT. Ablating only the localized defects removes less tissue than correcting a similar amount of regular astigmatism. This sparing of corneal tissue allows treatment of high levels of irregular astigmatism, simultaneously achieving a regular smooth surface.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, it was recently described 13 that eyes after CT can present higher UDVA gains than eyes with other diagnoses (such as decentered optic zone, among others), but that the gain of CDVA can present an opposite trend. 8 Actually, Allan and Hassan 8 observed that CDVA gain was lower in patients with irregular astigmatism after CT than after previous refractive surgery, describing a median gain of 0 lines for CT eyes. The authors justified these outcomes by the development of severe haze in a significant number of cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The high volume of excimer laser systems and the short learning curve could explain this high popularity. One of the advantages of the excimer laser, in general, is the ability to treat the wide range of postkeratoplasty refractive errors, including the irregular ones [6,36,37]. Another unique advantage is the ability to remove visually significant subepithelial fibrosis and scarring 'phototherapeutic keratectomy (PTK)' [38].…”
Section: Surface Ablationmentioning
confidence: 99%
“…Laser-assisted subepithelial keratectomy (LASEK), as an advanced surface ablation, has been also used in the past few years in an attempt to decrease the haze [6,41]. Customized topography-guided or wavefrontguided surface ablation has been tried for better refractive outcomes [35,37,[42][43][44].…”
Section: Surface Ablationmentioning
confidence: 99%